Pengaruh Kurs, Suku Bunga BI, Indeks STI, Indeks KLSE dan Indeks MC Terhadap Indeks Harga Saham Gabungan Di BEI Periode September 2014-Desember2015 - Melisa Puspita Dewi; Nurhayati Nurhayati; Hadi Paramu (UPT Penerbitan Universitas Jember, 2018)
The aims of this research are to analyze the influence of Strait Times Index, Kuala Lumpur Stock Exchange index, and Manila Composite index on strengthening or weakening relation of exchange rate and BI rate against Jakarta Composite Index from September 2014-December 2015. This research used secondary data and a quantitative research . The type of research used is explanatory research ,the population are stock price indices in Bursa Efek Indonesia and sample used is Jakarta Composite Index which shows daily prices fluctuation of all stocks. Analysis methode used is moderated regression analysis. The results showed Strait Times Index able to strengthen exchange rate with Jakarta Composite Index and unable to strengthen BI rate with Jakarta Composite Index, Kuala Lumpur Stock Exchange index able to strengthen exchange rate and BI rate with Jakarta Composite Index, last Manila Composite index unable to strengthen exchange rate with Jakarta Composite Index and able to strengthen BI rate with Jakarta Composite Index. Keywords: Strait Times Index, Kuala Lumpur Stock Exchange, Manila Composite, Indeks Harga Saham Gabungan, Moderated Regression Analysis.